Dampak QRIS Terhadap Kebiasaan Belanja Mahasiswa di Era Digital : Studi Kasus Mahasiswa STIA Lancang Kuning Dumai - Andi Riski Firnanda; Putri Sulisti; Hildawati Hildawati (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This research aims to examine the impact of QRIS (Quick Response Code Indonesian Standard) on students' shopping habits in the digital era, focusing on students at STIA Lancang Kuning Dumai. This study uses a qualitative approach with in-depth interviews and focus group discussions (FGD) to explore students' experiences and perceptions regarding QRIS use in their shopping activities. The findings indicate that QRIS has provided students with convenience, efficiency, and security in digital transactions, although some students face barriers related to technological literacy and network issues. QRIS has influenced shopping habits by encouraging more online shopping. These findings contribute to understanding the role of digital payment systems in changing students’ consumption behavior.